Risk assessment method for the organization of environmental safety in the sphere of residential and industrial construction - A. N. Larionov; E. E. Smirnova (Vestnik MGSU)
Introduction. The risk assessment method for the justification of environmental safety in construction is considered. The development of this topic is dictated by the need for sustainable development of the construction sector, prevention of environmental pollution, and improvement of the quality of life of the population. Despite the fact that the legal system has accumulated a sufficient volume of documents regulating the goals and objectives of preventing the negative impact of economic activity on the environment, as well as increasing the environmental efficiency of companies, methods for assessing environmental risk in construction are poorly developed.Materials and methods. The authors studied approaches for environmental risk assessment under conditions of uncertainty. The authors faced the task to find the optimal distribution of funds aimed at reducing the probability of occurrence of environmental risk, and funds for preventing possible environmental damage, as well as to analyze and compare methods for determining the amount of risk during the design and construction of facilities. The main goal was to conduct research on the formation of a complete algorithm and methodology for using risk scenarios to ensure environmental safety in construction. The object of the study was risk-oriented approaches to ensuring the environmental safety of construction projects. The subject was the application of risk assessment methods in the field of environmental safety. The concept of the need to use methods for reducing the environmental risk of construction projects is proposed.Results. A new method is developed that combines quantitative assessment of environmental risk based on probability theory, semi-quantitative approach with risk matrices, and qualitative assessment based on the assessment of the probability of occurrence and the size of damage for each scenario. The developed method for assessing environmental risk can improve the efficiency of environmental safety management in the construction industry.Conclusions. The significance of the scenario approach as one of the most effective methods for assessing environmental risk is emphasized, which allows taking into account possible scenarios of events and assess their consequences. It is necessary to develop a more accurate definition of environmental risk in construction when formulating environmental measures and assessing their compliance (it is possible to improve an analogue of the Japanese CASBEE ecological assessment system in construction).